2013
DOI: 10.7314/apjcp.2013.14.4.2545
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Views of Secondary School Students in Kuala Lumpur on Cervical Cancer and its Prevention

Abstract: Cervical cancer is one of the most frequent cancers in women worldwide. Persistent infection with a human papillomavirus (HPV) is the main cause for cervical cancer. Vaccination and Pap smear screening are the best methods for prevention of the disease. The objective of this cross-sectional study was to assess the knowledge and views of upper secondary school female students in Kuala Lumpur, Malaysia, toward prevention of cervical cancer. This study was conducted from April 2009 to September 2009 in 8 schools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 23 publications
2
15
1
3
Order By: Relevance
“…A total of 22 studies assessed knowledge, attitudes and beliefs towards vaccination programs [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] (Table 1), while 9 papers, two of which presented results obtained from the same study, assessed attitudes towards the Human Papilloma Virus (HPV) vaccine in young girls specifically (Table 2). 25,26,38,[44][45][46][47]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 22 studies assessed knowledge, attitudes and beliefs towards vaccination programs [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] (Table 1), while 9 papers, two of which presented results obtained from the same study, assessed attitudes towards the Human Papilloma Virus (HPV) vaccine in young girls specifically (Table 2). 25,26,38,[44][45][46][47]…”
Section: Resultsmentioning
confidence: 99%
“…There were 8 studies (9 papers) focusing on HPV vaccination, published between 2010 26,38,48,49 and 2016. 25 Half of the studies were performed in the USA, 26,38,44,48,49 one in Malaysia, 46 one in Guyana, 47 one in Nigeria 45 and one in Hungary. 25 Samples consisted of parents and caretakers of adolescents in a first group of studies, 26,38,44,49 students from high school in two studies, 25,46 both parents and children in one study, 47 and women over 18 years old in the two final studies.…”
Section: Hpv Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous international studies, disease awareness has a positive impact on the attitude of young adults toward HPV vaccination; thus, it must be considered as a protective factor [19,20,21]. There was also a positive association between knowledge, trust in the vaccine, and the number of received doses, which indicated that more trust in the vaccine resulted in higher acceptance [20,22].…”
Section: Discussionmentioning
confidence: 98%
“…Most of the participants who took part revealed that they heard about the cervical cancer (97%), 77% participants responded that they heard about pap smear test. Several studies reported that participants have heard about cervical cancer and pap smear test [11][12][13][14] .Media such as the television, radio, internet and etc (media) play a very important role in awareness of cervical cancer among women [15][16][17] . In our study we have found that different source of knowledge this can be due to the fact that most of the participants who took part in the study are in first year of medical course.…”
Section: Discussionmentioning
confidence: 99%